2014
DOI: 10.1590/0102-33062014abb3150
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and evolutionary relationships of Passiflora subg. Decaloba supersect. Decaloba sect. Xerogona (Passifloraceae): contributions of palynological, morphological and molecular studies

Abstract: Passiflora subg. Decaloba supersect. Decaloba sect. Xerogona (Passifloraceae) is a tropical and subtropical group comprising 14 species that occur in tropical biomes throughout Latin America, including the Atlantic Forest. The section Xerogona comprises herbaceous vines characterized by a lack of petiole glands on their leaves, of bracts and of ocelli on their leaf blades, as well as by their capsular fruits. We analyzed the phylogeny on the basis of morphological characters (including pollen characters) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…However, the last two species are closely associated with P. sexflora in the ncpGS tree. Additionally, these results are consistent with the ones found byKrosnick et al (2013) andMilward-de-Azevedo et al (2014) regarding their position in the series and they also support subgenus Decaloba as monophyletic.…”
supporting
confidence: 91%
“…However, the last two species are closely associated with P. sexflora in the ncpGS tree. Additionally, these results are consistent with the ones found byKrosnick et al (2013) andMilward-de-Azevedo et al (2014) regarding their position in the series and they also support subgenus Decaloba as monophyletic.…”
supporting
confidence: 91%
“…The shape of the leaves and the absence of floral bracts and laminar nectaries suggest affiliation with Passiflora sect. Xerogona, and a DNA analysis places the species as sister to the rest of the section (Krosnick et al, 2013;Milward-de-Azevedo et al, 2014b).…”
mentioning
confidence: 95%
“…Another issue is whether the thigmotropic androgynophore features are adaptively inherited for their potential role in the evolution of flower-pollinator relationships in Passiflora . It has been suggested that hummingbird-pollinated Xerogona species, such as P. citrina and P. sanguinolenta , are derived in relation to other insect-pollinated Decaloba species ( Milward-de-Azevedo et al ,, 2014 ). We therefore infer that the wide-moving androgynophores, characteristic of hummingbird-pollinated species (such as P. sanguinolenta ) are derived with respect to insect-pollinated species with more ‘restricted’ movement (such as P. capsularis ).…”
Section: Discussionmentioning
confidence: 99%